Analysing the development of the broadband ecosystem in the Republic of the Congo 2014–2018 - Kissangou, Jean Philemon (My University, 2020)
Broadband availability and access is a critical concern for the Republic of the Congo, as the acquisition of network infrastructures is of utmost importance for all countries aspiring to be competitive in an information-based economy, particularly developing countries. Broadband is an enabler of growth that has profitable synergistic effects in all sectors of life including health, education, banking and other economic sectors, government administration, and democracy. This study attempts to understand how policy and regulation affects the development of the broadband ecosystem in the Republic of the Congo. It considers ways in which policy and regulation may address the remaining gaps in broadband development. The case study adopted a qualitative approach, whereby documents including law and regulation were reviewed, and semi-structured interviews were conducted with selected knowledgeable respondents. The analysis of findings indicates that the broadband ecosystem would develop and allow individuals to enjoy broadband, if appropriate actions are taken through policy, electronic communications sector law, regulation, management, and development of relevant skills for broadband services and use. Only then, will the country put itself on track and enter the knowledge and information society, for the benefit of the majority of citizens. Such appropriate actions include a particular focus on the national backbone project, the rehabilitation of the ADSL infrastructure for the last mile part of the broadband network or replacement of the ADSL infrastructure with more advanced wireless technologies, and addressing the management and governance concerns within the state telecoms company
Research report submitted to the Faculty of Humanities, University of Witwatersrand in partial fulfilment of the degree of Master of Arts in the field of ICT Policy and Regulation, 2020